2017
DOI: 10.3390/genes8050144
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation Targets Influenced by Bisphenol A and/or Genistein Are Associated with Survival Outcomes in Breast Cancer Patients

Abstract: Early postnatal exposures to Bisphenol A (BPA) and genistein (GEN) have been reported to predispose for and against mammary cancer, respectively, in adult rats. Since the changes in cancer susceptibility occurs in the absence of the original chemical exposure, we have investigated the potential of epigenetics to account for these changes. DNA methylation studies reveal that prepubertal BPA exposure alters signaling pathways that contribute to carcinogenesis. Prepubertal exposure to GEN and BPA + GEN revealed p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 55 publications
(120 reference statements)
3
19
0
Order By: Relevance
“…Results of another study in a breast cancer animal model suggested that genistein treatment decreased the carcinogenic activity bisphenol A (BPA), a high-volume chemical that is used in the manufacturing of polycarbonate plastics and containers for foods and beverages [87]. The genistein treatment decreased the BPA induced promoter methylation of different tumor suppressor genes in breast cancer [87].…”
Section: Genistein and Daidzein Modulates Histone Modificationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Results of another study in a breast cancer animal model suggested that genistein treatment decreased the carcinogenic activity bisphenol A (BPA), a high-volume chemical that is used in the manufacturing of polycarbonate plastics and containers for foods and beverages [87]. The genistein treatment decreased the BPA induced promoter methylation of different tumor suppressor genes in breast cancer [87].…”
Section: Genistein and Daidzein Modulates Histone Modificationsmentioning
confidence: 99%
“…Results of another study in a breast cancer animal model suggested that genistein treatment decreased the carcinogenic activity bisphenol A (BPA), a high-volume chemical that is used in the manufacturing of polycarbonate plastics and containers for foods and beverages [87]. The genistein treatment decreased the BPA induced promoter methylation of different tumor suppressor genes in breast cancer [87]. Another study indicated that soy phytoestrogens such as genistein, daidzein, and equol lead to a reduction in trimethylation marks and an increase in acetylating marks of selected genes EZH2, BRCA1, ERα, ERβ, SRC3, and P300 [88].…”
Section: Genistein and Daidzein Modulates Histone Modificationsmentioning
confidence: 99%
“…Comparison of genes that are epigenetically altered in the rat mammary gland to predict breast cancer patient survival using the Cancer Genomic Atlas (TCGA) revealed that two genes, HPSE and RPS9, were hypomethylated in the mammary gland of rats prepurtertally treated with GEN or GEN + BPA and were also associated with increased patient survival (104). These findings and the in vitro studies above provide strong evidence that at least in the mammary gland, GEN may induce beneficial DNA methylation and other epigenetic changes.…”
Section: Epigenetic Changes Induced By Phytoestrogens or Bacterial Mementioning
confidence: 99%
“…Four genes were associated with a poor survival rate and eight were associated with a good survival rate. Among these genes, nine were hypermethylated in the distal region, indicating that their expression may be modified [ 62 ]. It should be noted that recent data suggest that BPA may act via ER-independent mechanisms including nuclear hormone receptors such as the thyroid hormone receptor, androgen receptor, and glucocorticoid receptor, but also with the orphan estrogen-related receptor gamma (ERRγ).…”
Section: Edcs and Breast Cancermentioning
confidence: 99%